Clinical and evolutive characteristics of patients rehabilitated with ocular prosthesis - Ana Margarita Vinent Céspedes; Mirtha Martí Pool; María Cristina Céspedes Quevedo (Centro Provincial de Información de Ciencias Médicas, 2021)
Introduction: Ocular prosthesis is an artificial means with functional and cosmetic ends that facilitates the physical, psychic and social rehabilitation of patients with eyes defects. Objective: To describe the evolution of patients with ocular prosthesis according to infection signs in the rehabilitated ocular cavities, associated risk factors, as well as modifications in the form of the cavity and/or in the ocular prosthesis  Methods: An observational, longitudinal and prospective study of 74 patients suffering from eye defects that received prosthetist treatment from 2018 to 2019 in the oral maxillofacial Rehabilitation Clinic was carried out in Santiago de Cuba, who were evaluated through a survey and a clinical exam in three moments during a year of evolution. To establish the association between variables, the Pearson chi-square and Fisher exact tests were used with the fulfillment of suppositions.  Results: Of the 222 exams made to the rehabilitated ocular cavities, 31 revealed the presence of secretions in 23 patients, with recurrence in 8 of them; this clinical sign became evident in a similar way to the hypercoloring of the conjunctiva  as for the moment of the finding and  the age group affected, with higher percentages at the year of evolution and a higher incidence in the patients of 60 years and over. Also, an association statistically significant of the daily hygiene of the cavity and prosthesis variables with the existence of secretions was verified, for a confidence interval of 95 %. Conclusions: The advantage of the ocular cavity and prosthesis weekly personal cleanliness was demonstrated, because with it the frequency of the inflammatory and infectious signs of the mucous is reduced, what should be strictly observed in elderly, who are the most affected.